2022
DOI: 10.1108/jbsed-07-2021-0102
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and income inequality

Abstract: PurposeTourism has grown to be one of the world's largest and fastest-growing economic industries. Tourism development is viewed as a tool to improve income distribution as it allows people at the bottom of the pyramid to get involved in the industry. This study aims to examine the impact of tourism on income inequality in the top income equality countries.Design/methodology/approachThe paper employs fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares techniques to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…(2020) for Malaysia, and several cross-country studies such as Alam and Paramati (2016) for developing economies, Raza and Shah (2017) for top 43 TA countries, Nguyen et al . (2021) for 97 countries, and Subramaniam et al . (2022) for the top 9 income equality countries [5].…”
Section: Empirical Results and Detailed Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…(2020) for Malaysia, and several cross-country studies such as Alam and Paramati (2016) for developing economies, Raza and Shah (2017) for top 43 TA countries, Nguyen et al . (2021) for 97 countries, and Subramaniam et al . (2022) for the top 9 income equality countries [5].…”
Section: Empirical Results and Detailed Discussionmentioning
confidence: 93%
“…For the cross-country studies, the negative influence of tourism on income inequality is found in the studies of Proença and Soukiazis (2008), Nguyen et al . (2021) and Subramaniam et al . (2022).…”
Section: Literature Review On Tourism Development and Income Inequalitymentioning
confidence: 98%
See 2 more Smart Citations
“…A relatively scant amount of rigorous work has been devoted to the tourism-income inequality nexus. Indeed, there is a relatively larger strand of the related literature, which has reported an inequality reduction effect of tourism (Li et al , 2016 for Chinese regions, Croes and Rivera, 2017 for Equador, Uzar and Eyuboglu, 2019 for the Turkish case, Nguyen et al , 2021 for a sample of 97 countries and Shahbaz et al , 2021 of the Malaysian case study, Chi, 2021 for a sample of 36 countries, Fang, 2021 for the case of 103 countries, Subramaniam et al , 2022 for a sample of top income equality countries and Chiu and Wang, 2022 for the 102 countries).…”
Section: Related Literaturementioning
confidence: 99%